2005
DOI: 10.1096/fj.05-4020fje
|View full text |Cite
|
Sign up to set email alerts
|

RNA interference targeting SHP‐1 attenuates myocardial infarction in rats

Abstract: The Src homology domain 2 (SH2)-containing tyrosine phosphatase-1 (SHP-1) plays a key role in apoptosis and decreases phosphorylation of Akt. Apoptosis of cardiomyocytes is thought to contribute to the increased area of acute myocardial infarction (AMI), and Akt activation exerts a powerful cardioprotective effect after ischemia. Thus, a therapeutic strategy designed to inhibit expression of SHP-1 would be beneficial in AMI. Here we report that siRNA targeting SHP-1 reduced infarct size in a rat model of AMI. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 32 publications
2
28
0
Order By: Relevance
“…We also demonstrate that SHP-1, but not its closest structurally related family member, SHP-2, is the specific phosphatase for GIV. This is in keeping with the fact that whereas SHP-1 antagonizes Akt signaling (18,(41)(42)(43)(44) and inhibits chemotaxis (27,(45)(46)(47)(48), SHP-2 is frequently associated with enhancement of the PI3K-Akt pathway (49 -53) during growth factor-initiated cell migration (54). Of note, all of the experimental evidence supporting SHP-1 ability to antagonize the Akt pathway was obtained using mesenchymal and hematopoietic cells and the biological role of the epithelium-specific isoform of SHP-1 and how it might inhibit chemotaxis/cell migration remained elusive (55).…”
Section: Discussionsupporting
confidence: 80%
“…We also demonstrate that SHP-1, but not its closest structurally related family member, SHP-2, is the specific phosphatase for GIV. This is in keeping with the fact that whereas SHP-1 antagonizes Akt signaling (18,(41)(42)(43)(44) and inhibits chemotaxis (27,(45)(46)(47)(48), SHP-2 is frequently associated with enhancement of the PI3K-Akt pathway (49 -53) during growth factor-initiated cell migration (54). Of note, all of the experimental evidence supporting SHP-1 ability to antagonize the Akt pathway was obtained using mesenchymal and hematopoietic cells and the biological role of the epithelium-specific isoform of SHP-1 and how it might inhibit chemotaxis/cell migration remained elusive (55).…”
Section: Discussionsupporting
confidence: 80%
“…The PCR products were analyzed by agarose gel electrophoresis (1.3%) followed by staining with ethidium bromide and scanning with Gel-Doc (Bio-Rad). For semiquantitative PCR, GAPDH was used as an internal control to evaluate total RNA input, as previously described by our group (38).…”
Section: Methodsmentioning
confidence: 99%
“…47 Therefore, we examined the possible interaction of SHP-1 and ATIP and found that AT 2 receptor stimulation increases the formation of ATIP and SHP-1complex and their translocation into the nucleus and enhances cell differentiation in rat neurons. 38 In contrast, Sugano et al recently demonstrated that treatment with small interfering RNA (siRNA) against SHP-1 in acute myocardial ischemia markedly reduced the infarct size 48 and accelerated angiogenesis through increased phosphorylation of KDR/flk-1, 49 suggesting that knocking down of SHP-1 has beneficial effects on ischemic disease. However, the involvement of Ang II in these experiments is not clear.…”
Section: Shp-1mentioning
confidence: 98%